2013
DOI: 10.1038/jid.2012.395
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-Hydroxyvitamin D and Risk of Non-Melanoma and Melanoma Skin Cancer: A Prospective Cohort Study

Abstract: Sun exposure is a major risk factor for skin cancer and is also an important source of vitamin D. We tested the hypothesis that elevated plasma 25-hydroxyvitamin D (25-OH-vitD) associates with increased risk of non-melanoma and melanoma skin cancer in the general population. We measured plasma 25-OH-vitD in 10,060 white individuals from the Danish general population. During 28 years of follow-up, 590 individuals developed non-melanoma skin cancer and 78 developed melanoma skin cancer. Increasing 25-OH-vitD lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 35 publications
(40 reference statements)
7
53
0
Order By: Relevance
“…Furthermore, as our cohort consists of white Danes living in Denmark with less sun exposure than those closer to the equator, our findings would be most relevant for individuals with a similar level of sun exposure and for similar 25(OH)D concentrations. The delay in measurement from 1981-1983 to 2009 -2010 could raise the concern of potential decay of plasma 25(OH)D, but several observations makes this highly unlikely: we noticed the expected seasonal variation of 25(OH)D concentrations; we found a strong association with skin cancer as expected with a reliable 25(OH)D measurement (27 ); median concentrations of plasma 25(OH)D across plasma samples from 3 different examinations on the same healthy participants with storage times of 10, 20, and 30 years were similar (27,28 ); previous studies have shown high stability during storage (40 ); the median concentration observed in our study of 16 ng/mL (41 nmol/L) was similar to that in comparable populations (16,19 ), and a low sample quality for the 25(OH)D measurement would tend to weaken rather than inflate an association. Finally, residual confounding cannot be ruled out as a potential explanation for our findings, because this is an observational study.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, as our cohort consists of white Danes living in Denmark with less sun exposure than those closer to the equator, our findings would be most relevant for individuals with a similar level of sun exposure and for similar 25(OH)D concentrations. The delay in measurement from 1981-1983 to 2009 -2010 could raise the concern of potential decay of plasma 25(OH)D, but several observations makes this highly unlikely: we noticed the expected seasonal variation of 25(OH)D concentrations; we found a strong association with skin cancer as expected with a reliable 25(OH)D measurement (27 ); median concentrations of plasma 25(OH)D across plasma samples from 3 different examinations on the same healthy participants with storage times of 10, 20, and 30 years were similar (27,28 ); previous studies have shown high stability during storage (40 ); the median concentration observed in our study of 16 ng/mL (41 nmol/L) was similar to that in comparable populations (16,19 ), and a low sample quality for the 25(OH)D measurement would tend to weaken rather than inflate an association. Finally, residual confounding cannot be ruled out as a potential explanation for our findings, because this is an observational study.…”
Section: Discussionmentioning
confidence: 52%
“…After applying inclusion criteria, 20 papers were left for analysis [25][26][27][28][29][30][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [28,[38][39][40] (392 CM cases overall) reported measures of melanoma risk across categories of increasing 25(OH)D serum levels: these were metaanalysed to yield a non-significant SRR of 1.46 (95% CI 0.60-3.53) for highest versus lowest categories (Fig. 2), with I 2 = 54%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations